Foreign body in the esophagus: a review - Ashraf, Omer (São Paulo Medical Journal, 2006)
Foreign body in the esophagus is a common emergency presentation. The approach towards a patient with a foreign body in the esophagus comprises a thorough history and systematic examination followed by relevant investigations. However, there is considerable debate over the most appropriate treatment option for such patients. This review aims to develop a comprehensive approach towards patients presenting with foreign body ingestion by developing clinical practice guidelines. These guidelines address not only the initial evaluation of the patient but also the various management alternatives and their advantages, limitations and applicability in various scenarios, based upon a review of the literature.